Microwave-assisted hydrosilylation of polypropylene and its application to in-situ grafted polypropylene/SiO2 nanocomposites. (8th September 2018) - Chammingkwan, Patchanee; Toyonaga, Masahito; Wada, Toru; Terano, Minoru; Taniike, Toshiaki
Abstract: Grafting end-functionalized polypropylene (PP) to the surfaces of nanoparticles is a promising approach in boosting physical properties of PP-based nanocomposites. In this study, a practical pathway is presented for the fabrication of PP-grafted nanocomposites: Reactive silicon alkoxy groups were introduced through microwave-assisted hydrosilylation of terminal unsaturation of vis-breaking PP. Thus obtained hydrosilylated PP was added as a reactive additive in melt compounding of PP with SiO2 nanoparticles to implement in-situ grafting. Significant improvements were attained in the dispersion of SiO2 nanoparticles, the crystallization rate and the tensile strength.